The Relationship between Type 2 Diabetes and Platelet Indicators - Xiangyu CHEN; Le FANG; Hongbo LIN; Peng SHEN; Tao ZHANG; Hui LI; Xiaoyong LI; Min YU; Chunxiao XU; Jie ZHANG; Feng LU; Xiaofu DU; et al. (Tehran University of Medical Sciences, 2017)
Background: Currently, the studies on the relationship between type 2 diabetes and platelets indicators were carried out on a selective small sample population generally. Large sample studies in this area are rare, especially in Chinese population. In this study, we aimed to investigate the relationship between type 2 diabetes and the mean platelet volume (MPV), platelet count (PLT) and platelet distribution width (PDW). Methods: This is a cross-sectional analysis of the routine health examination data from 20128 participants with complete baseline data in Yinzhou District 2013. The detection of indicators in this study was completed by automatic hematology analyzer. Results: The PDW and PLT were not significantly different between diabetic group and non-diabetic group, (16.00% vs. 16.00%, P=0.88, and 194*109/L vs. 196*109/L, P=0.05 respectively). The MPV was significantly higher in diabetic group (9.3fl vs. 9.2fl, P<0.05). MPV was an independent risk factor of diabetes mellitus (Unadjusted OR=1.07 (95% CI: 1.03, 1.11), Adjusted for age, sex OR=1.07 (95% CI: 1.02, 1.12)). The adjusted odds ratio of diabetes rose with increasing MPV levels and were most pronounced in subjects with MPV levels exceeding the 90th percentile (MPV≥10.70 fl, Crude or=1.23 adjusted or=1.19). Conclusion: There was no relationship between the presence of diabetes with PDW and PLT. The MPV was independently associated with the presence of diabetes.